Resistance (at all costs) : how Trump haters are breaking America - Strassel, Kimberley A (Twelve, 2019)
"Among the most consistent and aggressive criticisms of Donald Trump is that he is a threat to American democracy -- a human wrecking ball demolishing our most basic values and institutions. Resistance (At All Costs) makes the opposite case -- that it is Trump's critics, in their zeal to oppose the president, who are undermining our foundations... [This book] shows that the reaction to Trump will prove far more consequential and damaging to our nation long-term than Trump's time in office."--Dust jacket flap.